Lateral Interbody Fusion for Treatment of Discogenic Low Back Pain: Minimally Invasive Surgical Techniques. (3rd April 2012) - Marchi, Luis; Oliveira, Leonardo; Amaral, Rodrigo; Castro, Carlos; Coutinho, Thiago; Coutinho, Etevaldo; Pimenta, Luiz
Abstract : Low back pain is one of the most common ailments in the general population, which tends to increase in severity along with aging. While few patients have severe enough symptoms or underlying pathology to warrant surgical intervention, in those select cases treatment choices remain controversial and reimbursement is a substancial barrier to surgery. The object of this study was to examine outcomes of discogenic back pain without radiculopathy following minimally-invasive lateral interbody fusion. Twenty-two patients were treated at either one or two levels (28 total) between L2 and 5. Discectomy and interbody fusion were performed using a minimallyinvasive retroperitoneal lateral transpsoas approach. Clinical and radiographic parameters were analyzed at standard pre- and postoperative intervals up to 24 months. Mean surgical duration was 72.1 minutes. Three patients underwent supplemental percutaneous pedicle screw instrumentation. Four (14.3%) stand-alone levels experienced cage subsidence. Pain (VAS) and disability (ODI) improved markedly postoperatively and were maintained through 24 months. Segmental lordosis increased significantly and fusion was achieved in 93% of levels. In this series, isolated axial low back pain arising from degenerative disc disease was treated with minimally-invasive lateral interbody fusion in significant radiographic and clinical improvements, which were maintained through 24 months.